2008
DOI: 10.1590/s1516-44462008000100003
|View full text |Cite
|
Sign up to set email alerts
|

Trial-Based Thought Record (TBTR): preliminary data on a strategy to deal with core beliefs by combining sentence reversion and the use of analogy with a judicial process

Abstract: Trial-Based Thought Record (TBTR): preliminary data on a strategy to deal with core beliefs by combining sentence reversion and the use of analogy with a judicial process Registro de Pensamentos com Base no Processo (RPBP): dados preliminares de uma estratégia para lidar com crenças nucleares, combinando reversão de sentenças e analogia com o processo jurídico

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 4 publications
2
34
0
4
Order By: Relevance
“…The first study on the efficacy of the TBTR in changing dysfunctional CBs and their corresponding emotions was conducted 7 , and significant results (p < 0.001) were observed in the adherence to CBs and associated emotions of 30 patients, reinforcing the hypothesis that this technique could, at least temporarily, contribute to the weakening of unhealthy CBs and their related emotions. Subsequently, the intensity of patients' dysfunctional CBs and corresponding emotions after the first use of the TBTR was assessed in a larger sample (n = 166) 8 , confirming the previous findings.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The first study on the efficacy of the TBTR in changing dysfunctional CBs and their corresponding emotions was conducted 7 , and significant results (p < 0.001) were observed in the adherence to CBs and associated emotions of 30 patients, reinforcing the hypothesis that this technique could, at least temporarily, contribute to the weakening of unhealthy CBs and their related emotions. Subsequently, the intensity of patients' dysfunctional CBs and corresponding emotions after the first use of the TBTR was assessed in a larger sample (n = 166) 8 , confirming the previous findings.…”
Section: Introductionmentioning
confidence: 82%
“…One of its main techniques is the trial-based thought record (TBTR), an intervention aimed at modifying dysfunctional CBs by simulating a legal trial. TBTR incorporates elements from various techniques already known in standard CBT and other psychotherapeutic approaches 7 . The patient has the opportunity to role-play him/herself not only as the defendant, but also as the prosecutor and the defense attorney, as well as a member of the jury, as opposed to what usually happens when dysfunctional CBs are activated 5 .…”
Section: Introductionmentioning
confidence: 99%
“…11 A more recent study of SAD patients who received 12 to 20 2-hour CBGT sessions concluded that, although symptoms of SAD and some aspects of QoL improved for up to 12 months after CBGT, the social functioning domain did not change, suggesting the need for better treatments for this condition. 12 The trial-based thought record (TBTR), 13 a novel approach used in trial-based cognitive therapy (TBCT), 14 was developed to address negative core beliefs (CBs) in CBT. In TBTR, the therapist engages the patient in a simulation of a legal trial, stimulating the activation of negative CBs and associated negative emotions, with the aim of reducing their effect with disconfirming evidence.…”
Section: Introductionmentioning
confidence: 99%
“…32 This method might be useful in restructuring negative beliefs in depressed patients. Despite the lack of clinical trials comparing this method with other psychological approaches used to treat depression, case reports indicate its potential in this regard.…”
Section: Trial-based Thought Record (Tbtr)mentioning
confidence: 99%